Regional economic outlook - International Monetary Fund. (Washington, D.C. : International Monetary Fund)
Strong fundamentals should allow Europe to weather financial turbulence relatively well. Nonetheless, growth is set to ease in 2008 in nearly all countries. Policymakers will need to deal up front with the financial market turmoil, while implementing fiscal consolidation and structural reforms, including in the financial sector, to address vulnerabilities, raise medium-term growth prospects, and deliver on the promise of convergence for emerging Europe. Three analytical chapters discuss reforms to strengthen Europe's financial systems to allow advanced economies to benefit from innovation with
Library has Nov. 2007
Some issues have also individual theme titles.
oif oif 06/02/2015
Ref.
Keywords: Economic forecasting; Economic conditions; Economic policy; Economic history; Latin America; North America; Caribbean Area